Association of oxytocin receptor gene polymorphisms rs53576 and rs2254298 with depression: a systematic review - Bittencourt Jacondino, Camila (2014)
AIMS: Although the etiology of depression is known to be multifactorial, studies have pointed to its association with a mutation in the oxytocin receptor gene (OXTR). The aim of this study was to determine, by means of a systematic review of the literature, whether OXTRs rs53576 and rs2254298 are associated with depression and depressive symptoms or temperament. METHODS: The survey was conducted on the databases Lilacs, PubMed, SciELO, Web of Science, Scopus and Embase, covering the period 2004-2014, in English and Portuguese, with the descriptors receptor da ocitocina/oxytocin receptor gene, added to depressão/depression, temperamento depressivo/depressive temperament, or distúrbios do humor/mood disorder. The following criteria were used for the inclusion of items: original studies with content available in full in English or Portuguese language; only human studies with clinical diagnosis of depression, or screening for symptoms and depressive temperament; studies on the variants rs53576 or rs22524298 of OXTR; and search for association between OXTR polymorphisms and depression and/or depressive symptoms or temperament. RESULTS: Initially 126 articles were captured, but only eight studies met the inclusion criteria. Of the eight articles included, six studies found a significant association between variants OXTR rs53576 and rs225298 with depression, mood and depressive symptoms, while two studies found no association. CONCLUSIONS: The results suggest that OXTR rs53576 and rs2254298 are associated with depressive symptoms and temperament as well as with depression. However, it should be noted that these polymorphisms do not act deterministically; rather, they are influenced or modulated by the environment, which may involve biopsychosocial, affective, ethnic, and gender factors.